PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO KASUS DUA KECAMATAN DI KABUPATEN SOLOK - , Pefi Aike Yandra ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The need for electricity is one of the basic needs of community that should be met by government. There are still many peoples unable to enjoy the electricity provided by government due to the limited capacity of government. Therefore, the government expects the active role of community to generate ideas and innovation to handle such limitedness. Micro-hydro power plant (MPP) is one of alternatives to meet the communityâs need for electricity. In Indonesia, the construction of MPP is largely failed than successful. The failure is generally caused by the lack of community participation in the management of existing MPP. MPPs in Jorong Aia Angek and Jorong Muaro Busuak, Solok Regency, are built on the ideas and proposals of community by funds from PNPM-MPd involving the community in the construction of MPP. The purposes of this study are to identify the level of success in the construction of MPP, analyze the level of community participation in the construction of MPP, and analyze the relationship between the level of success in the construction of MPP and the level of community participation in the construction of MPP in the two locations. The study was conducted by using deductive qualitative and quantitative approaches with a survey method. In discussing the success in the construction of MPP, the variables in the study were the construction of MPP, output produced, variables influencing the success ofperformance in development activities, i.e. leadership, resources, communication in the construction of MPP observed in the steps of planning, implementation, utilization and maintenance, categorized based on the Arnsteinâs classification. The relationship between the level of success in the construction of MPP and the level of community participation was analyzed by using a qualitative analysis technique. The results of the study indicate that the construction of MPP in Jorong Muaro Busuak was more successful than that in Jorong Aia Angek in view of the comparison of the outputs produced. This was influenced by leadership, resource, communication and coordination, fund allocation, regulation, and community participation. Community participation at the planning step of the construction of MPPin Jorong Aia Angek and Muaro Busuak based on the Arnstein classification was the level of partnership, at the implementation step in Jorong Aia Angek was at the level of placation, while in Jorong Muaro Busuak at the level of delegated power, and at the utilization and maintenance step in Jorong Aia Angek was at the level of placation, while in Jorong Muaro Busuak at the level of citizen control. The relationship between the level of success in the construction of MPP and the level of community participation in the two locations of study was positive, i.e. the success of development achieved was resulted from the support of community participation at each step of the construction of MPP. Keywords: community participation, construction of MPP